Is leaders’ mood contagious to team members? The mediator role of team mood and team potency in the relationship between leaders’ mood and team performance. - Fortes-Ferreira, Lina (2015)
Comunicação apresentada no 17º Congresso da European Association of Work and Organizational Psychology, 20-23 de maio de 2015, Oslo, Noruega